Internalisasi Nilai Karakter dalam Pembelajaran SBdP - Fitri Kurniawati; Peni Susapti (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to determine the internalization of values ​​in the implementation of Arts and Culture learning, the challenges faced in internalizing values, and the influence of internalization of values ​​on student character. The research method used is a qualitative description with a literature review approach. The results of this study describe the implementation of internalization of values ​​carried out in various ways and has an impact on the formation and strengthening of student character, although there are challenges experienced in the implementation of internalization of values. Manuscripts obtained from Google Scholar were filtered into ten journals covering MI, MIN, and SD educational units so that the data obtained are more valid in describing the internalization of values ​​in educational units. Challenges in implementing internalization of values ​​include technological developments that cause children to forget traditional games, the implementation of internalization of values ​​is still in the preparation stage, the lack of appreciation for local batik and batik is only local content in thematic modules without a specific curriculum, easily influenced by foreign cultures, lazy attitudes in drawing batik, limited natural materials, students focus on artistic techniques and ignore moral values, and limited learning time. Nevertheless, internalization of values ​​in Arts and Culture learning has a positive influence on the formation of student character.